PHYSICAL CHARACTERISTICS, RUMEN FERMENTATION PRODUCTS AND IN-VITRO DIGESTIBILITY OF NONI LEAVES (Morinda citrifolia) SILAGE USING DIFFERENT INOCULUMS - R. M., Taqwa; Mariani, N. P.; Mudita, I M. (Jurnal Peternakan Tropika, 2020)
This study aims to determine the physical characteristics, rumen fermentation products and in-vitro digestibility silage of noni leaves ( Morinda citrifolia ) using different inoculums. This study was conducted at the Research Station of Sesetan and the Laboratory of Nutrition and Animal Feed, Faculty of Animal Husbandry, Udayana University from June to September 2019. The design used was a completely randomized design (CRD) consisting of five treatments namely the silage of noni leaves without inoculum as a control (A), using Effective Microorganism 4 as inoculum combination of microorganism ( EM-4 ) (B), using inoculum Saccharomyces cerevisiae (yeast) (C), using inoculum Bacillus sp. strain BT 3 CL (D) and using inoculum Bacillus subtilis strain BR 2 CL (E) and each treatment had three replications.The observed variables were physical characteristics (density, water solubility and water absorption), rumen fermentation products (VFA and N-NH 3 ) and in-vitro digestibility (KcBK and KcBO). Research shows that using various kinds of inoculums (B, C, D and E) increase physical characteristics (density, solubility and water absorption), digestibility (KcBK and KcBO) and rumen fermentation products (VFA and N-NH 3 ) of noni leaves. Using inoculum bacteria (D and E) produced the highest density each 0,42 g/ml and 0,43 g/ml, and treatment D produced the highest water solubility of 33,63%. The inoculum combination of microorganism (B) produced noni leaves silage with highest water absorption, in-vitro digestibility (KcBK and KcBO) and rumen fermentation products (VFA and NNH 3 ) each 205,08%, 71,32%, 72,55%, 126,19 mM and 15,37 mM. Based on these result can conclude that noni leaves silage fermented by inoculum combination of microorganism (EM-4/ treatment B) has highest water absorption, in-vitro digestability and rumen fermentation product. Keywords: noni leaves, inoculum, digestibility, fermentation product, physical characteristics, silage